FROM IMAGINATION TO REPRESENTATION: UTILIZING LEONARDO.AI IN THE CONCRETIZATION OF GERMAN-LANGUAGE POETRY TO ENHANCE STUDENT CREATIVITY - Aini, Desti Nur; Aulia Rizky El Firsy, Gusti Aditiyawarman (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The era of digital transformation presents new opportunities for students to develop their imagination and creative capacity by integrating artificial intelligence into literary learning, particularly in the appreciation of cross-cultural literary works. This study aims to describe the potential use of artificial intelligence: Leonardo.Ai, in enriching the learning experience and strengthening the appreciation of cultural values through the concretization of German poetry into visual images. The research highlights the meaning of the visualization of the poem “Abseits” by Theodor Storm by students of the German Language Education study program at the State University of Malang by focusing on three main dimensions: aesthetics, interpretation, and creativity. Descriptive qualitative method was used in this research. The source of data is active students taking the “Literaturgeschichte course class of 2020. The research data is in the form of student interpretation results in interpreting poetry visualization. The data were collected through a questionnaire sheet. Data analysis was carried out with the stages of data reduction, data presentation, conclusion drawing. The results showed that in the aesthetic dimension, students were able to interpret the meaning of poetry through visual elements such as color, composition, and visual harmony. In the interpretation dimension, students can connect the symbolism and themes contained in the poem with the visual representation produced. The creativity dimension is shown by students through the variety of approaches and innovations in combining visual and textual elements to create unique and in-depth interpretations of poetry. The implication of the research results is that AI can be used as a supporting medium in learning literature, encouraging student creativity, which ultimately provides a significant contribution in the field of education.